Adaptation of anti-cea hybridomas cell line to serum free culture medium by using slow adaptaion technique - Marina, Maria Steven Imbahrajoo (2017)
In animal cell culture, serum is normally added in the cell culture medium to provide cells growth, regulates cell membrane permeability and also serves as a carrier for lipids, enzymes, micronutrients, and trace elements into the cell. However, serum has many drawbacks such as batch to batch variability, high price, interference with the purification of recombinant product, and the possibility of viral contamination. To address those threats, removal of serum from the culture medium is often carried out. In this study, a hybridoma cell line producing humanized antibody against the carcinoembryonic antigen or anti-CEA, will be adapted in a serum-free culture medium (SFM) by the slow adaptation technique. Cells were cultured in culture medium that is composed of serum supplemented medium (SSM) and SFM at varying ratios (100:0; 95:5; 90:10; 85:15 and 80:20). The technique was assessed by determining the cell density, cell viability as well as the glucose uptake and lactate release of the cells. Results indicated that the cell concentration was significantly reduced as the concentration of serum was decreased (when SSM: SFM ratio increases), and therefore the technique was considered as not compatible for adapting the specific cell line in SFM.